2021
DOI: 10.1186/s13064-021-00154-0
|View full text |Cite
|
Sign up to set email alerts
|

A two-step actin polymerization mechanism drives dendrite branching

Abstract: Background Dendrite morphogenesis plays an essential role in establishing the connectivity and receptive fields of neurons during the development of the nervous system. To generate the diverse morphologies of branched dendrites, neurons use external cues and cell surface receptors to coordinate intracellular cytoskeletal organization; however, the molecular mechanisms of how this signaling forms branched dendrites are not fully understood. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…HPO-30, by binding to actin filaments and the WRC at the same locations on the membrane, would promote the formation of more highly branched actin networks, likely in a manner analogous to CapZ ( Figure 6 , bottom). This dual actin binding ability could be one mechanism by which the swellings at branch points observed in PVD neurons are formed (Shi et al, 2021). Further investigation into how the HPO-30 ICD binds to both the WRC and actin will potentially reveal a new class of proteins that can regulate multiple steps of the actin polymerization process, allowing for greater control of local actin dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HPO-30, by binding to actin filaments and the WRC at the same locations on the membrane, would promote the formation of more highly branched actin networks, likely in a manner analogous to CapZ ( Figure 6 , bottom). This dual actin binding ability could be one mechanism by which the swellings at branch points observed in PVD neurons are formed (Shi et al, 2021). Further investigation into how the HPO-30 ICD binds to both the WRC and actin will potentially reveal a new class of proteins that can regulate multiple steps of the actin polymerization process, allowing for greater control of local actin dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction recruits the WRC to the membrane and simultaneously promotes WRC activation by Rac1, which in turn stimulates Arp2/3 to produce branched actin filaments. In (4), the dual actions of HPO-30 ICD cooperatively promote the formation of branched actin networks, which can cause the "swelling" of dendrite observed in previous studies (Shi et al, 2021), an important prerequisite for the outgrowth of a new dendrite branch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dendrite filopodia are structurally distinct from conventional filopodia, with an unusual network-like cytoskeletal organization characterized by both branched and linear filaments of mixed polarity (Korobova and Svitkina, 2010), suggesting involvement of multiple actin regulatory proteins with distinct activities. Few studies have identified specific actin regulators involved in forming new branches (Hou et al, 2015; Nithianandam and Chien, 2018; Shi et al, 2021; Sturner et al, 2022; Sturner et al, 2019; Zou et al, 2018), and none have pinpointed their regulation of actin to the location and timing of nascent branch outgrowth. In sensory neurons of living Drosophila larvae, the locations of dendrite filopodia initiation sites are pre-figured by patches of actin polymer (Andersen et al, 2005; Nithianandam and Chien, 2018; Sturner et al ., 2019), as has been proposed for dendrite filopodia in the mouse brain also (Willig et al, 2014).…”
Section: Introductionmentioning
confidence: 99%